Fatal neonatal septicemia with meningitis due to Escherichia coli in a full-term baby: an unusual presentation - Chandpara, Prakash P.; Bhatt, Ritu M.; Marathe, Anant P.; Mehta, Vaidehi J.; Nakshiwala, Neha (International Journal of Research in Medical Sciences, 2025)
Neonatal meningitis carries the risk of long-term debilitating squeal with very high mortality. With the use of antibiotics, the mortality due to neonatal meningitis has significantly reduced in developing countries, with India reporting incidence rates of 0.5 per 1000 with mortality ranging from 16-34%. Diagnosis of neonatal meningitis is based on clinical presentation, gestational age, causative agent, and geographical location. Early empiric antibiotic therapy may often obscure the diagnosis of the causative agent. We report a fatal case of neonatal meningitis in a 39-day-old baby. The child was initially treated for hyperbilirubinemia and mild fever. The child presented with a fever for 4 days and episodes of convulsion. The child was put on ampicillin and gentamicin empirically. The CSF was suggestive of pyogenic meningitis. The Gram-stained smear of the CSF sediments revealed Gram-negative bacilli suggestive of E. coli (Enteric-like gram-negative bacilli). E. coli was isolated from blood as well as CSF and was a phenotypically ESBL (CTX-M like) producer. The antibiotic was changed to meropenem and amikacin. Despite appropriate antibiotic therapy, the patient rapidly deteriorated and died on the third day of admission. Treatment of bacterial meningitis due to E. coli in neonates has changed over the years due to the emergence of antibiotic resistance patterns of E. coli. Resistance to third-generation cephalosporin has evolved in E. coli due to ESBL production. Neonatal meningitis due to E. coli, particularly in full-term babies, is reported rarely. We report a case of fatal meningitis due to ESBL-producing E. coli in a full-term baby.